2002
DOI: 10.1210/me.2001-0290
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Inducibility of the Human Na+/H+Exchanger Regulatory Factor/Ezrin-Radixin-Moesin Binding Protein 50 (NHE-RF/EBP50) Gene Involving Multiple Half-Estrogen Response Elements

Abstract: The Na+/H+ exchanger regulatory factor (NHE-RF; also known as ezrin-radixin-moesin binding protein 50) is a primary response gene under estrogen receptor (ER) control that may provide a link between estrogen action and the regulation of cytoskeletal and cell-signaling pathways. These studies were undertaken to define the human NHE-RF genomic regions and regulatory sequences mediating its robust estrogen responsiveness. Screening of a human genomic library yielded NHE-RF clones comprising the full gene, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 57 publications
4
26
0
Order By: Relevance
“…As noted earlier, NHERF1 possesses an estrogen response element (Ediger et al, 1999(Ediger et al, , 2002. Thus, high correlation between NHERF1 and estrogen receptor expression comes as no surprise (Stemmer-Rachamimov et al, 2001;Cardone et al, 2007;Song et al, 2007;Wheeler et al, 2011).…”
Section: Breast Cancermentioning
confidence: 71%
See 1 more Smart Citation
“…As noted earlier, NHERF1 possesses an estrogen response element (Ediger et al, 1999(Ediger et al, , 2002. Thus, high correlation between NHERF1 and estrogen receptor expression comes as no surprise (Stemmer-Rachamimov et al, 2001;Cardone et al, 2007;Song et al, 2007;Wheeler et al, 2011).…”
Section: Breast Cancermentioning
confidence: 71%
“…Other steroid hormones were without effect, and antiestrogens blocked the stimulatory action of estradiol. Further analysis revealed that although NHERF1 does not possess a canonical estrogen response element, it contains numerous ERE half-sites (TGACC and GGTCA) (Ediger et al, 2002). Subcloning of the 3.5 kilobases of the 5Ј-flanking region, which contains all 13 ERE half-sites, in a CAT reporter and cotransfection with the estrogen receptor ␣ in MDA-MB-231 breast cancer cells displayed a 29-fold stimulation in response to estradiol.…”
Section: Hormonal Regulation Of Namentioning
confidence: 99%
“…It also contained the ER-responsive gene coding for NHE-RF/EBP50/SLC9A3R1 protein, which inhibits cell migration by scaffolding ERM proteins and regulating their link with the actin cytoskeleton (Ediger et al, 2002). In perfect agreement, this gene is overexpressed in non-invasive vs invasive BCL (Schindelmann et al, 2002).…”
Section: Expression Profiling Of Breast Cell Lines E Charafe-jauffretmentioning
confidence: 99%
“…Whereas in vitro experiments have suggested anti-proliferative functions of EBP50, 14 -16 a positive correlation between EBP50 expression, estrogen receptor status, and tumor progression has been found in human breast cancer. 9,10 Of particular interest with respect to biliary pathophysiology, the major regulators of EBP50 expression are estrogens, 4,17 which are known to target the biliary tree, where they modulate the proliferative activities of cholangiocytes. 18 -20 In the present study, we examined the expression of EBP50 and binding partners in the human liver, under normal conditions and in the setting of biliary disorders, ie, in different types of human cholangiopathies and after bile duct ligation (BDL) in rats.…”
mentioning
confidence: 99%